Life notations of Daisy Sweeney: Reflections of othermothering, musicianship and Montreal - Campbell, Arlene (Université York, 2012)
The life story of Mrs. Daisy Sweeney, an African Canadian native of Montreal, Quebec, helps fill a void in the historical documentation of Montreal Blacks (especially female elders). Of particular significance is her prominence as a music educator and othermother during her life. The current literature on African Canadian othermothering experiences is not synonymous with both White or African American females and inclusion of their voices in academic, as well as mainstream spaces, is virtually non-existent. This dissertation asks: What did it mean to be a first generation 'Negro' working class bilingual female in a largely hostile White francophone Quebec metropolis in the early 20th Century? How can her narratives help shape and inform life history and African Canadian othermothering research? My sojourn with Mrs. Daisy Sweeney referenced African centered epistemology in my conceptual understanding of herself and community mothering. Capturing her conversations meant engaging with multiple methodologies articulated through African oral traditions, life history, archival canons and interdisciplinary inquiries. It is striking to note that there were not only certain tensions associated with memory loss and physical limitations (prompted by the aging process) that destabilized and enriched our 'interactive' communication, but also revealed a rupture and reversal of the participant/researcher dynamic. In spite of blatant racial discrimination that plagued Montreal's Black communities during that time, Daisy Sweeney fulfilled a life-long dream and taught hundreds of children the canon of classical piano for over 50 years. She lived her voice through her music, finding ways to validate her own identity and empowering others in the process. She used the musical stage as her platform to draw invaluable connections between race, gender, language and social class. Daisy Sweeney's generation of othermothers is dying out and, as the carriers of culture, the urgency to tell their stories must be emphasized. The account respects, reclaims and reflects those voices. It is time to write in African Canadian female elders and diversify the exclusionary genre of life history and archival research.
http://hdl.handle.net/10315/31697
Keywords: 1900-1999; DIG; afro-féminisme; amériques; approches et analyses; discipline; femmes* noires; histoire et politique; maternité; montréal; musique; mémoires/thèses; philosophie; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; travail

Colères de femmes noires et excès narratifs dans Passing de Nella Larsen, Sula de Toni Morrison et Push de Sapphire - Gibeau, Ariane (Université du Québec à Montréal, 2012)
Le présent mémoire s'intéresse aux représentations de la colère dans la littérature des femmes africaines-américaines du 20e siècle. Il cherche à comprendre de quelles manières cette émotion taboue et honteuse investit Passing de Nella Larsen, Sula de Toni Monison et Push de Sapphire, trois œuvres écrites à différentes époques-clés de l'histoire littéraire noire états-unienne au féminin (les années 1920 et la Renaissance de Harlem; les années 1970 et l'émergence du féminisme noir et de sa critique littéraire; les années 1990 et la consécration institutionnelle des black women's studies). Il s'agit de voir comment, dans ces romans où prédominent des enjeux liés aux oppressions de sexe, de race et de classe, la colère joue le rôle de moteur textuel, d'émotion-source : elle dirige les actions et propos des personnages, dirige les intrigues, dirige l'écriture. Elle semble ainsi constituer une impulsion, un paradigme traversant la tradition littéraire féministe noire. L'étude d'un corpus diachronique permet d'entrevoir une évolution singulière : le passage d'une colère nommée et thématisée à une colère-discours. La colère constituant une émotion du désordre et du spectaculaire, j'analyse les stratégies narratives qui permettent de faire surgir l'excès et le théâtral dans les œuvres à l'étude. Ma réflexion se décline en quatre temps. Je me penche dans un premier chapitre sur les articulations entre rapports d'oppression et colère. J'interroge les liens entre sexe et colère, puis entre race et colère, pour enfin présenter les fondements théoriques du féminisme noir et les écrits de féministes noires sur la question. Les trois autres chapitres sont consacrés aux romans analysés : le deuxième traite de Passing et de la colère qui prend possession de l'intrigue grâce à quelques stratégies du double; le troisième montre que la colère, dans Sula, se manifeste selon deux mouvements simultanés (une transmission entre plusieurs générations de personnages et un détournement dans la narration) et par le recours à la métaphore du feu; le quatrième s'intéresse à Push et à son esthétique de l'excès, laquelle imprègne à la fois les corps des protagonistes et la narration. ______________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : colère, excès, violence, littérature afro-américaine, littérature américaine, féminisme noir, Nella Larsen, Toni Morrison, Sapphire.
Keywords: 1900-1999; IREF; afro-féminisme; approches et analyses; discipline; féminismes noirs; mémoires/thèses; périodes historiques; ressource en ligne; études littéraires